1979
DOI: 10.1039/f19797501487
|View full text |Cite
|
Sign up to set email alerts
|

Infrared spectra of carbon monoxide adsorbed on transition metal cation exchanged tin(IV) oxide

Abstract: For carbon monoxide adsorbed in the coordination spheres of five transition metal cations (Cr3+, Mn3+, Co2+, Ni2+, Cu+) in the tin(1v) oxide surface, correlations are found between the stretching frequency and the (calculated) electric field strength at the adsorption site and between the stretching frequency and the integrated band intensity. The bonding between carbon monoxide and the adsorption sites present on metal oxide surfaces is discussed in view of these correlations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

1979
1979
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…These geminal polycarbonyls easily lose one (or more) of their CO ligands during evacuation at 85 K thus being converted into Mn 2þ -CO linear species. Analysis of the literature data [20,23,24,27,28] indicates that the oxidation state of manganese in the carbonyl complexes is indeed 2+.…”
Section: Adsorption Of Co On Mn-zsm-5mentioning
confidence: 99%
See 2 more Smart Citations
“…These geminal polycarbonyls easily lose one (or more) of their CO ligands during evacuation at 85 K thus being converted into Mn 2þ -CO linear species. Analysis of the literature data [20,23,24,27,28] indicates that the oxidation state of manganese in the carbonyl complexes is indeed 2+.…”
Section: Adsorption Of Co On Mn-zsm-5mentioning
confidence: 99%
“…IR bands due to Mn nþ -CO surface complexes have been recorded at 2213-2172 cm À1 [20][21][22][23][24][25][26][27][28] and at 2144-2114 cm À1 [21,22,29]. These vibrations are generally assigned to Mn 2þ -CO species [20,23,24] but some authors [21,25,29] have reported that they characterise Mn 3þ -CO carbonyls.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Extensive IR studies have been carried out to study this reaction [3][4][5] and to explore the surface reactions occurring at the tin(IV) oxide surface upon CO adsorption [6]. The experiments were carried out on oxide samples with and without transition metals as tin(IV) oxide itself has been shown to catalyze the oxidation of CO with 02 [7].…”
Section: Introductionmentioning
confidence: 99%
“…IR measurements carried out on tin(IV) oxide containing transition metals identified mainly physisorbed CO and different carbonate species adsorbed at the metal ion site [4]. Metal dependent v(CO) bands were detected in the IR spectrum and their frequencies were correlated with the calculated electric field strength at the adsorption site [5]. Nevertheless, it could not be unambiguously established whether species of the type M-CO and/or M-O ...CO were present.…”
Section: Introductionmentioning
confidence: 99%